Preferensi Konsumen Terhadap Pembelian Santan Instan di Lambaro Kecamatan Ingin Jaya Kabupaten Aceh Besar - Ulfa, Nadiatul; Puspita, Diah Eka; Khumaira, Khumaira; Fitri, Sri (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
The rapid development of technology has caused people to look for a practical material, one of which is the manufacture of ready-to-use instant coconut milk. Currently, instant coconut milk is widely circulated on the market with various types. The purpose of this study is to find out which attributes are consumer preferences and considerations in the decision to buy instant coconut milk. The research method used was quota sampling (according to the criteria) with a sample of 24 respondents. The data analysis model used is Fishbein Multiattribute analysis. Based on the results of the study, instant coconut milk that is the preference of consumers is instant coconut milk with attributes that are the choice of consumers including the Sun Kara brand, liquid texture, 200 ml packaging, and a price of Rp6,000 - Rp12,000. In order of attributes from the most considered to the least considered attributes are brand, texture, ease of obtaining, place, packaging, and price.